Studi Fenomenologi Pemahaman Orang Tua Terhadap Pendidikan Anak di Pondok Pesantren Ma’hadul Muta’allimin Katerban Ngawi - M. Zainal Abidin; Ahmad Ali Riyadi; Irmawan Jauhari (CV. Lentera Literasi Indonesia, 2025)
The aim of this research is to study phenomena that occur in society and find out how parents consider the Ma'hadul Muta'allimin Katerban Ngawi Islamic boarding school as an educational choice for their children. This research focuses on parents' understanding of how they choose Islamic boarding schools as an educational choice for their children. This study analyzes phenomenology from the perspective of social construction theory. The research collected data through observation, documentation and in-depth interviews. This research was conducted at Ma'hadul Muta'allimin, an educational institution that offers formal education and religious knowledge in one place. The research results show that the Ma'hadul Muta'allimin Katerban Ngawi Islamic boarding school is an Islamic educational institution that offers religious and formal education which continues to change according to the demands of the times. Internal factors, such as family culture and parental education, and external factors, such as teenagers' interactions, the reality of society, and parents' busy lives, including parental considerations, such as religious and formal education, and full supervision from the Islamic boarding school management.